Engineering cell-adhesive gellan gum spongy-like hydrogels for Regenerative Medicine purposes - Silva, Lucília Pereira (2014)
The similarity between the extracellular matrix of soft tissue and hydrogels, characterized by high-water-content viscoelastic polymeric networks, has been sustaining the advancement of hydrogels for tissue engineering and regenerative medicine (TERM) purposes. Current research on hydrogels has focused on introducing cell-adhesive peptides to promote cell adhesion and spreading, a critical applicability limitation. Here we report the development of gellan gum (GG) spongy-like hydrogels with ameliorated mechanical performance and flexibility in relation to hydrogels, using a simple and cost-effective method. Most importantly, these materials allow the entrapment of different cell types representing mesenchymal, epidermal and osteoblastic phenotypes that spread within the three-dimensional microstructure. This effect was associated with microstructural rearrangements characterized by pore wall thickening and pore size augmentation, and lower water content than precursor hydrogels. These properties significantly affected protein adsorption once cell adhesion was inhibited in the absence of serum. Spongy-like hydrogels are not adhesive for endothelial cells; however, this issue was surpassed by a pre-incubation with a cell-adhesive protein, as demonstrated for other substrates but not for traditional hydrogels. The proposed cell-compatible GG-based structures avoid time-consuming and expensive strategies that have been used to include cell-adhesive features in traditional hydrogels. This, associated with their off-the-shelf availability in an intermediary dried state, represents unique and highly relevant features for diverse TERM applications.